The Rate of Pyrite Oxidation Study by Thiobacillus ferrooxidans in Acid Mine Drainage Problem - AHSAN BUSYAIRI (NIM : 10613003), MAULANA
Acid mine drainage (AMD) can form when a certain ferrous-sulfide is oxidized and reacts with water. Its appearance in post-mining activities hard to be detected due to lag time, therefore a long period of time is needed to monitor and mitigate its impact. This research aims to be the option to accelerate the reaction of ferrous-sulfide oxidation, pirit in particular, using biological agent Thiobacillus ferrooxidans. The oxidation efficiency of pirit was determined by the presence of Fe3+ ions in the Extracellular Polimeric Substance of Thiobacillus ferrooxidans. The Fe3+ ions excalation was done by adapting Thiobacillus ferrooxidans and adding galactose in the growth medium used. In this research, the PAF overburden from PT Adaro Indonesia category LC and MC were pre-characterized with several tests, such as; XRF, XRD, static geochemistry, and SEM. Bacteria spray treatment (A) and bacteria with galactose spray treatment (G) on the overburden LC and MC were conducted using bioaugmentation and biostimulation method in 30 day period. The pH, and Fe2+ and SO42-concentration of the leachate was measured using Free Draining Leach Column Test system. Kinetic test result of treatment A bioaugmentation, the pH of PAF overburden LC and MC reached NAGpH value in 1 day and 9 days, respectively. In biostimulation treatment, the pH of PAF LC treatment A and G reached NAGpH value in 2 days, meanwhile the MC from all treatment did not reached NAGpH value at all. Oxidation rate of Fe2+ dan SO42- ions were faster with treatment G, whether using biostimulation or bioaugmentation method. In conclusion, treatment (A) using bioaugmentation method showed that its pH value was almost as much as the NAGpH value. Treatment (G) was faster in decreasing Fe2+ dan SO42- ions in leachate, whether using biostimulation or bioaugmentation method.